(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to shed light on the nature of the tax gap in the income tax by the method of direct deduction and its reflection on the financial objective of the tax, and to determine the reasons for this gap in the deduction between the tax due in accordance with the laws and instructions in force and the tax actually paid. The tax gap is a real problem that cannot be ignored for what it represents loss of financial revenues due to the state. The research problem is represented in the existence of a gap between the tax due according to direct deduction instructions and the tax actually paid according to the financial statements, and to achieve the objectives of the research and test the hypotheses, the descriptive and analytical approach was used, the researcher recalculated the income tax imposed on a sample of employees of the Diyala Education Directorate, and calculated the tax gap between the tax due and the tax actually paid. One of the most important findings of the researcher in the practical side is the existence of a tax gap between the tax due and the tax paid, and the most prominent factors leading to this difference are the inaccuracy of the tables sent by the General Tax Authority to government sector departments, and the low efficiency The professionalism of some accountants based with deduction, one of the most prominent recommendations recommended by the researcher is to amend the direct deduction tax schedules issued by the General Tax Authority in line with direct deduction instructions No. (1) for the year 2007 and in the interest of the tax community and the General Tax Authority alike, , In addition to employing information technology through the use of an accounting program that can calculate the withholding tax and terminate these calculation errors to reach the full collection of the tax due.